2022
DOI: 10.3390/cimb44030085
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Home-Applied Dual-Light Antibacterial Photodynamic Therapy Can Reduce Plaque Burden, Inflammation, and aMMP-8 in Peri-Implant Disease—A Pilot Study

Abstract: Until now, in clinical dentistry, antibacterial photodynamic therapy (aPDT) has been restricted to in-office treatments, which hampers repeated applications. This pilot study tested the benefit of a commercially available Lumoral® device designed for regular periodontal dual-light aPDT treatment at home. Seven patients with peri-implant disease applied dual-light aPDT daily in addition to their normal dental hygiene for four weeks. A single Lumoral® treatment includes an indocyanine green mouth rinse followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…In the NSPT group, less than 2/3 of patients reduced the number of deep pockets, and 1/3 of patients reduced the number of deep periodontal pockets by 50% or more. These results are in agreement with our previously reported effects of regular dual-light treatment, where a significant reduction in aMMP-8, BOP, and VPI were seen in periodontal patients with intensive, regular, up to twice daily, Lumoral® use [9]. Similarly, a recently published case report showed a significant improvement in periodontal disease status after regular Lumoral® use in a patient with difficulties in the mechanical performance of oral hygiene at home [15].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the NSPT group, less than 2/3 of patients reduced the number of deep pockets, and 1/3 of patients reduced the number of deep periodontal pockets by 50% or more. These results are in agreement with our previously reported effects of regular dual-light treatment, where a significant reduction in aMMP-8, BOP, and VPI were seen in periodontal patients with intensive, regular, up to twice daily, Lumoral® use [9]. Similarly, a recently published case report showed a significant improvement in periodontal disease status after regular Lumoral® use in a patient with difficulties in the mechanical performance of oral hygiene at home [15].…”
Section: Discussionsupporting
confidence: 92%
“…However, not surprisingly, because in most studies, the treatment has been applied sparsely, actually, in most studies only once or twice [7,8]. The treatment has appeared more effective in studies which have reported repetitive aPDT treatment [9][10][11]. Thus, the frequency of treatment can have a significant effect on the response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings also-for the first time-demonstrate that aMMP-8 PoCT is a quantitative online and real-time biomarker to be well-implemented in the new staging and grading classification of periodontitis in patients receiving radiotherapy for their head and neck cancer [47]. Noteworthy, aMMP-8 PoCT-technology can thus be well adapted to quantitatively real-time online and quantitatively chairside monitor and follow the outcomes of the emerging host modulating treatments [110,120,121]. Further studies are warranted in this area.…”
Section: Link Between Ammp-8 Levels and The Periodontal Tissue Destru...mentioning
confidence: 59%